Analisis Kepuasan Konsumen Pada Kopi Lain Hati Manado (Hati 463, Jl. Jendral Sudirman No. 96, Komo Luar, Kecamatan Wenang) - Nuraziizah, Zulfaa; Mandei, Juliana Ruth; Loho, Agnes Estephina (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze consumer satisfaction with Manado's Lain Hati coffee. This research was conducted from April to June 2022. The data used are primary data and secondary data. Primary data was obtained through direct interviews with 30 respondents using a questionnaire. Secondary data obtained through business owners, the internet and other sources related to this research. The results showed that customer satisfaction of Kopi Lain Hati Manado through the variables of product, price, place, promotion and service quality, achieved a total score of 2,500 which indicated a consumer satisfaction index number of 83.33% and was classified as satisfied. There are two variables that have the highest level of satisfaction, namely the service quality variable of 87.33% belonging to the very satisfied category and the product variable of 86.40% belonging to the very satisfied category. While other variables, namely the promotion variable of 81.00%, the price of 80.00%, and the place of 79.66% which are classified in the satisfied category. This shows that consumers are generally satisfied with all the variables from Kopi Lain Hati Manado.